Character of Education in Pesantren Perspective: Study of Various Methods of Educational Character at Pesantren In Indonesia - Zaenal Arifin; Moh. Turmudi (Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
This article is the result of study focused on discussing the various of educational character methods in Indonesian pesantren. Where judging from the history of the pesantren is actually an educational institution that has holistic and integrative potential. During this time pesantren have played a strategic role in planting character values ​​in society. This character can be seen from the tradition of Islamic education in pesantren which is prioritizes processes rather than the results. Trust in baraka for pesantren is alleged to be a pioneer of planting character values. But so far, character education that was developed in formal schools by the Indonesian government, in fact, did not involve the pesantren and or did not pay much attentions to the results of research concerning character education in pesantren in particular and the tradition of boarding education in general. So that research becomes very urgent to continue to exploring the potential of pesantren in terms of planting character values ​​continuously. The results of this study indicate that there are four variants of the method of character education in pesantren, namely; hidden curriculum, habituation, ta’zir tradition (punishment), real life, exemplary, application of religious culture, and barakah is indicated as psychologycal reward.